The effect of Phyllanthus niruri and Catharanthus roseus on Macrophage Polarization in Breast Cancer Mice Model: The Effect of P. niruri and C. roseus in Breast Cancer Mice Model - Sakti, Sefihara Paramitha; Sari, Fikriya Novita; Rachmawati, Farida; Widyarti, Sri; Rahayu, Sri; Soewondo, Aris; Jatmiko, Yoga Dwi; Rifa'i, Muhaimin (Journal of Tropical Life Science, 2024)
Cancer death cases have increased yearly, and there are estimated to be 21.6 million cancer cases in 2030. Studies of herbal compounds for cancer treatment alternatives are essential because cancer treatment is relatively expensive and has adverse effects. Phyllanthus niruri (Pn) and Catharanthus roseus (Cr) are plants that are known as herbal medicines. Combining the two plants is expected to prevent and enhance the immune system in breast cancer cases. This study aims to analyze the anti-cancer and immunomodulatory effects of P. niruri and C. roseus extract (PCE) in modulating macrophage polarization in breast cancer mice. Experimental animals are divided into six groups and there is healthy control (normal mice), cancer (DMBA-induced mice), cancer mice with cisplatin administration, cancer mice with PCE administration with three different doses, including dose 1 (500 mg/kg Pn + 15 mg/kg Cr), dose 2 (1000 mg/kg Pn + 75 mg/kg Cr), and dose 3 (2000 mg/kg Pn + 375 mg/kg Cr). The mice were injected with DMBA once a week for six weeks to induce cancer in mice. The breast cancer mice model was administered with PCE orally for 14 days. The expression of CD11b+IL-10+ and CD11b+IFN-γ+ demonstrated macrophage polarization. The results showed that breast cancer induction using DMBA increased the level of IL-10 and decreased the level of IFN-γ significantly compared to the normal group (p < 0.05). In specific doses, administration of PCE could reduce IL-10 levels and increase the level of IFN-γ significantly (p < 0.05). PCE can modulate the polarization of macrophages by suppressing the M2-like macrophage and increasing the M1-like macrophage. The ability of PCE to modulate macrophage polarization indicates that the combination of P. niruri and C. roseus has activity as an anti-cancer.